Acceleration Based Activity Levels During Subacute Inpatient Stroke Rehabilitation. (2017) - Murphy, Margit Alt; Andersson, Sofi; Danielsson, Anna; Ohlsson, Fredrik; Wipenmyr, Jan
Abstract: People after stroke have difficulties to reach sufficient physical activity level during their rehabilitation and particularly outside the therapy time. We aim to quantify activity levels and investigate differences in motor activity in weekdays and weekends in a subacute stage after stroke. Data from multiple three-axis accelerometers was collected during two 48 h sessions in 11 patients. The activity level and symmetry indices were sensitive to variations in weekend and weekdays. This information is valuable in rehabilitation planning and management and enables identification of those in risk of low physical activity and inactivity.